The Characteristics of A1-A2 β-Caseins in Milk and Their Effects on Human Health - Sema Yaman Fırıncıoğlu; Hatice Nur Kılıç (Turkish Journal of Agriculture: Food Science and Technology)
Despite positive effects on nutrition, it has been reported that milk causes allergic reactions and many health problems. Allergic reaction to milk is called lactose intolerance, but it is estimated that this is not caused by lactose, but by the β -casein structure of milk, which varies depending on animal species. Although there are many fractions of β-casein in the structure of milk, especially A1 and A2 casein attract attention. A1 β -casein causes many health problems because it plays a role in the formation of the bioactive opioid peptide β-casomorphin-7 (β-CM-7). These health problems are allergic reactions, weakening of the immune system and slowing down of the gastro-intestinal system and some systemic diseases (cardiovascular disease, type 1 diabetes, autism, schizophrenia). The underdevelopment of gastro-intestinal system, especially in newborns, causes us to encounter these health problems more frequently. For this reason, the consumption of milk containing A1 β-casein, especially cow’s milk from culture breeds, is not recommended. Since BKM-7 (β-casomorphin-7) formed by A1 β-casein cannot occur in A2 β-casein, these health problems cannot be expected to be observed. However, A2 β-casein causes DPP4 (dipeptidyl peptidase 4) enzymes to be regulated in the body and a non-opioid effect is observed. It is recommended to consume goat’s milk and dairy products containing A2 β-casein in newborns, people with celiac disease and stomach disorders. Despite the lack of studies on the subject of A1 and A2 β-casein and the ongoing discussions, in this review, the importance and differences of A1 and A2 β-caseins in cow and goat milk were discussed and their effects on human health.